English Literature in the Digital Era: Transformations and Trends - Sanganand Bagde (Emerging Trends in Languages, 2025)
English literature context has been changed significantly with modernisation of the digital age that is creating a massive impact on creation, dissemination, and interpretation of literature. When one considers the relationship between literature and digital innovation, one may summarize these disruptive forces as both a challenge to and opportunity for literature — a hybridization of past forms. It explores how digital technologies have transformed reading practices, textual analysis, and the work of criticism, while highlighting the nascent field of digital humanities. The study also discusses how multimodal texts, participatory narratives, and digital storytelling challenge conventional literary structures and encourage new forms of participation and creation. Digital innovation, making literary spaces more accessible and democratic, is, on the other hand, also a process that dilutes creativity, genuineness, and does something to the role of academic literary studiers. By analyzing significant technological advancements and their effects on modern literature, this study demonstrates the transformative potential of digital innovation in redefining English literature in the twenty-first century. Digital platforms foster evolving interpretive frameworks that reshape narrative engagement across diverse audiences. Interactive archives, algorithmic curation, virtual authorship, and collaborative annotation introduce expanded modes of literary interaction. Machine-assisted reading, immersive environments, adaptive storytelling, and networked discourse further reconfigure textual boundaries. These emerging practices cultivate fluid meanings, innovative creative expressions, and dynamic scholarly perspectives that collectively redefine contemporary literary culture.
Keywords: artificial intelligence; digital innovation; information technology; reading culture; social media